The Influence of Electronic Word of Mouth and Brand Image on The Purchase Decision of Video on Demand Netflix Subscription: (Study On Netflix Users In Medan City) - Gultom, Monica Desyderya; Adlina, Hafiza; Siregar, Onan Marakali (Talenta Publisher, 2023)
ABSTRACT: The Covid-19 pandemic has caused changes in everyone. These changes have influenced the communication industry which created the concept of Video On Demand. Netflix is one of the streaming services that have a variety of shows such asmovies, anime, documentaries, and many more. During the first time, Netflix came to Indonesia, they had many issues with government and public services. The purpose of this research is to analyze the effect of electronic word of mouth (E-WOM) and brand image on the purchase decision of Netflix subscriptions in Medan city. The research used an associative method with a quantitative approach. The sample andpopulations in this research are 100 people who have used Netflix in Medan City. Data were collected using a survey method and then analyse by using simple linier regression. The results of the research conducted indicate that the E-WOM variable (X1) has no significant effect on purchasing decisions. Meanwhile, the brand image variable (X2) has significantly influenced buying decisions. However, E-WOM and brand image have an equal (simultaneous) effect on purchase decisions (Y). The result of the correlation coefficient (R) of 0.836, where this coefficient value shows the relationship between E-WOM and brand image on purchasing decisions.